A response surface methodology approach to crafting superior performance of potassium salt-based solid biopolymer electrolytes - Adam, Abdullahi Abbas; Soleimani, Hassan; Dennis, John Ojur; Aldaghri, Osamah A.; Alhathlool, Raed; Eisa, M.H.; Ibnaouf, Khalid Hassan; Abdulkadir, Bashir Abubakar; Usman, Fahad; Zango, Zakariyya Uba; Isa, Mannawi Nasiru; Muhammad Fadhlullah, Abd Shukur (Elsevier Ltd, 2024)
In this study, we developed an eco-friendly solid electrolyte by blending pectin (PT) with methylcellulose (MC) and complexed with potassium carbonate (K2CO3) salt and ethylene carbonate (EC) plasticizer. The goal of the study was to understand the salt-plasticizer interaction and to optimize the electrochemical performance using response surface methodology (RSM) within the central composite design (CCD). RSM approach unveiled that K2CO3 and EC interact significantly, impacting the ionic conductivity and potential window of the solid biopolymer electrolytes (SBEs). After optimization, this work achieved ideal conditions with 35.05 wt% K2CO3 and 16.78 wt% EC, yielding an ionic conductivity of ~ 1 × 10-3 Scm− 1 and a 4.77 V potential window. Structural analysis confirmed coordination among constituents and increased amorphous content. This work, therefore, highlights PT/MC/K2CO3/EC’s potential for electrochemical device applications. An electrochemical cell constructed using the optimized sample exhibited the highest specific capacitance of 50.74 Fg–1 , as determined by cyclic voltammetry (CV) analysis.